Victimization and Vilification of Romani Children in Media and Human Rights Organizations Discourses - Christianakis, Mary (Social Inclusion, 2015)
Through an analysis of European newspapers, human rights organization reportage, and United Nations documents and websites, this article examines how public discourse regarding education, human rights, poverty, child rearing, and child labour manufactures a dangerous, implausible childhood for Romani children. These discourses, perpetrated by human rights organizations and news media, leverage the languages of intervention, cultural difference, nationalism, and social justice to simultaneously victimize and vilify Romani children, rendering them incapable of experiencing humane childhoods. Employing critical discourse analysis and systemic functional grammar analysis, the proposed article seeks to disentangle the discourses of human rights for Roman children from the assimilationist arguments aimed at compulsory schooling and Eurocentric family and labour practices rooted in access to middle class dominant labor markets.